Predictors of efficacy of androgen-receptor-axis-targeted therapies in patients with metastatic castration-sensitive prostate cancer: A systematic review and meta-analysis. (July 2020) - Buonerba, Carlo; Ferro, Matteo; Dolce, Pasquale; Crocetto, Felice; Verde, Antonio; Lucarelli, Giuseppe; Scafuri, Luca; Facchini, Sergio; Vaia, Angelo; Marinelli, Alfredo; Terracciano, Daniela; Montella, Liliana; et al.
Abstract: Background: Both docetaxel and androgen-receptor-axis-targeted (ARAT) agents are approved in metastatic castration-sensitive prostate cancer (mCSPC) patients. Predictive factors of therapy efficacy are lacking. Methods: We included articles reporting data about randomized-controlled clinical trials (RCTs) testing an ARAT agent plus ADT vs. ADT. We aimed to obtain pooled estimates of efficacy outcomes and assess differences in pooled estimates of efficacy outcomes between sub-groups. Results: A total of 5427 mCSPC patients enrolled in five RCTs were evaluable for OS (Overall Survival) and PFS (Progression-free survival). Pooled OS-HR (Hazard Ratio) was 0.66 (95 % CI: 0.60−0.74), while pooled PFS-HR was 0.46 (95 % CI: 0.40−0.53). Combined treatment with docetaxel was associated with differential OS outcomes, while tumor volume according to the CHAARTED criteria and visceral metastasis were associated with differential PFS outcomes. Conclusion: Our results add evidence that ARAT agents improve OS in mCSPC and discourage their combined use with docetaxel in this setting.